Student Learning Outcomes Assessment in Higher Education and in Academic Libraries: A Review of the Literature - Goss, Harold (The Journal of Academic Librarianship, 2022)
Conducting effective assessment toward evaluating student learning outcomes (SLO) is a difficult and complex process for all higher education professionals. University-level conversations are increasingly centered on student learning outcomes as they pertain to issues such as students' skills competence, continuous improvement, retention, etc. In response to the increasing demand for units on campus (including academic libraries) to contribute to these conversations, an understanding of how to assess student learning outcomes becomes essential. This paper reviews recent academic literature pertaining to assessing student learning outcomes in higher education and academic libraries. The objective is to use both to create a starting point for academic librarians looking to embark on a SLO-based program of assessment at their academic libraries.
Keywords: Academic libraries; Assessment; Information literacy; Librarians; Student learning outcomes; Student success